1998
DOI: 10.1016/s0735-1097(98)00473-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics determining the mode of presentation in patients with acute coronary syndromes

Abstract: The clinical presentation of acute coronary syndromes may be influenced by various factors that have the potential to influence the coagulability of the blood, the collateralization of the coronary circulation and myocardial mass. Myocardial infarction is favored by cigarette smoking, advanced age and renal impairment, while unstable angina is favored by treatment with aspirin, hypertension, previous revascularization and previous coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 33 publications
3
7
0
2
Order By: Relevance
“…Smokers have a heightened thrombotic response. Therefore, as observed here, proportionally fewer smokers present with non-STsegment elevation acute coronary syndromes [18].…”
Section: Smoking and Type Of Acute Coronary Syndromesupporting
confidence: 76%
See 1 more Smart Citation
“…Smokers have a heightened thrombotic response. Therefore, as observed here, proportionally fewer smokers present with non-STsegment elevation acute coronary syndromes [18].…”
Section: Smoking and Type Of Acute Coronary Syndromesupporting
confidence: 76%
“…Indeed, it has already been reported that smoking is associated with ST-segment elevation among patients admitted with acute coronary syndromes [18,19]. In the setting of ST-segment elevation myocardial infarction, a fibrin-rich thrombus produces a stable clot, which leads to complete and sustained coronary occlusion.…”
Section: Smoking and Type Of Acute Coronary Syndromementioning
confidence: 99%
“…We can list four typical clinical situations. First, cigarette smokers have a significantly increased risk of acute coronary syndrome [49] and a high likelihood of developing thrombosis [50]. The increased thrombotic tendency observed in smokers might be the basis of acute coronary syndromes in them.…”
Section: Calcium Metabolism Hormones and Smokingmentioning
confidence: 99%
“…This is consistent with past reports and is believed to be related to the heightened thrombotic response of smokers. 7,18, 19 Smokers have lower rates of other risk factors of coronary artery disease, such as diabetes mellitus, hypertension, and CKD. 20 Smokers with ACS present an average of 8 years earlier with fewer risk factors and a lower incidence of multivessel disease, in agreement with past reports.…”
Section: Discussionmentioning
confidence: 99%